2009
DOI: 10.1007/s00330-009-1331-8
|View full text |Cite
|
Sign up to set email alerts
|

Can microvessel invasion of hepatocellular carcinoma be predicted by pre-operative MRI?

Abstract: Microvessel invasion is a major prognostic factor in hepatocellular carcinoma (HCC) that influences the suitability of surgery, but rarely can be evaluated preoperatively. This study was performed to identify preoperative MRI findings that reflect histopathological microvessel invasion in hepatocellular carcinoma. Gadobenate dimeglumine-enhanced four-arterial phase dynamic study and hepatobiliary phase images of preoperative MRI of 70 HCC lesions were retrospectively reviewed. Tumor size (cm), peritumoral enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
127
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 161 publications
(143 citation statements)
references
References 19 publications
13
127
3
Order By: Relevance
“…They reported that wedge-shaped enhancement could be due to nontumorous arterioportal shunts rather than tumorous ones and it was not a statistically significant risk factor for MVI; on the other hand, irregular circumferential peritumoral enhancement could be a preoperative predictor of MVI. The sensitivity, specificity, positive predictive value, and negative predictive value of irregular circumferential peritumoral enhancement in the prediction of MVI were 74.3%, 82.9%, 81.3%, and 76.3%, respectively (16). The crucial point in their study was obtaining four arterial-phase MRI scans at the same level.…”
Section: Peritumoral Enhancementmentioning
confidence: 98%
See 4 more Smart Citations
“…They reported that wedge-shaped enhancement could be due to nontumorous arterioportal shunts rather than tumorous ones and it was not a statistically significant risk factor for MVI; on the other hand, irregular circumferential peritumoral enhancement could be a preoperative predictor of MVI. The sensitivity, specificity, positive predictive value, and negative predictive value of irregular circumferential peritumoral enhancement in the prediction of MVI were 74.3%, 82.9%, 81.3%, and 76.3%, respectively (16). The crucial point in their study was obtaining four arterial-phase MRI scans at the same level.…”
Section: Peritumoral Enhancementmentioning
confidence: 98%
“…They also reported that the presence of an intact capsule on CT was closely correlated with the absence of MVI (13). In a different study authors reported that there was no significant correlation between MVI and presence of radiologic capsule (16). On the other hand, Adachi et al (17) reported that a fibrous capsule was a predictor of portal venous invasion since cancer cells frequently invade the vessels of the fibrous capsule.…”
Section: Capsulementioning
confidence: 99%
See 3 more Smart Citations